Prevention of Fraud to Achieve Accountability For Village Fund Management - Mufidah Mufidah; Netty Herawaty (Universitas Batanghari Jambi, 2023)
The study aims to analyze the influence of internal control and competence on fraud prevention to achieve accountability for village fund management in pandemic times. Internal control and competence of village officials become one of the challenges in this pandemic period where the village government is more efficient and effective in using the budget. But there are still factors that cause reduced accountability in the management of village funds caused by the change of village heads that bring an overhaul of their leadership structure. In addition, there are still many activities that are not in accordance with Permendes priority.This resulted in one of the causes of weak internal control and competence possessed by the village apparatus. This study used Purposive sampling in Muaro Jambi district as many as 50 respondents. This research is quantitative research with a causality research design. Cross-section data types and primary data sources. Data analysis techniques using SEM-PLS. The results showed that internal control significantly affects fraud prevention directly, and indirectly affects accountability. Conversely, competence does not affect fraud prevention and does not affect either directly or indirectly on accountability for village fund management. Fraud prevention affects accountability of village fund management.